Computed tomography angiography/magnetic resonance imaging-based preprocedural planning and guidance in the interventional treatment of structural heart disease - Bertsche, Dagmar; Rottbauer, Wolfgang; Rasche, Volker; Buckert, Dominik; Markovic, Sinisa; Metze, Patrick; Gonska, Birgid; Luo, Erfei; Dahme, Tillman; Vernikouskaya, Ina; Schneider, Leonhard M. (Frontiers in Cardiovascular Medicine, 2022)
Preprocedural planning and periprocedural guidance based on image fusion are widely established techniques supporting interventional treatment of structural heart disease. However, these two techniques are typically used independently. Previous works have already demonstrated benefits of integrating planning details into image fusion but are limited to few applications and availability of the proprietary tools used. We propose a vendor-independent approach to integrate planning details into periprocedural image fusion facilitating guidance during interventional treatment. In this work, we demonstrate the feasibility of integrating planning details derived from computer tomography and magnetic resonance imaging into periprocedural image fusion with open-source and commercially established tools. The integration of preprocedural planning details into periprocedural image fusion has the potential to support safe and efficient interventional treatment of structural heart disease.